Sex, 'Race, ' and Betrayal: Kalinda Sharma and Bisexual Feminist Politics. Issue 3 (2nd July 2016) - Taylor, Leonie
ABSTRACT: The bisexual woman is a key site of contestation in theorizing a feminist sexual politics. Paradoxically, she can be situated as either a source of liberation or a source of oppression. Acknowledging this ambiguity, the author examines to what extent female bisexuality can theorize a liberatory feminist sexual politics from three angles: pleasure and desire, queer alliance building, and 'race.' Challenging bisexual stereotypes, the author shows how bisexual women are framed within a phallocentric lesbian feminist consciousness and considers how the racialization of bisexuality complicates its radical potential. The author considers the threatening nature of bisexual women through Hemmings' theory of the bisexual 'double agent' and the character of Kalinda Sharma from the CBS television series The Good Wife . The author uses these productive limitations of bisexuality to imagine a liberatory feminist sexual politics, exploring to what extent the unbiased nature of bisexual desire defies misogyny and heteronormative logic.